Immediate acoustic effects of straw phonation exercises in subjects with dysphonic voices. (April 2013) - Guzman, Marco; Higueras, Diego; Fincheira, Catherine; Muñoz, Daniel; Guajardo, Carlos; Dowdall, Jayme
Abstract This study sought to measure any acoustic changes in the speaking voice immediately after phonation exercises involving plastic straws versus phonation exercises with the open vowel /a/. Forty-one primary school teachers with slightly dysphonic voices were asked to participate in four phonatory tasks. Phonetically balanced text at habitual intensity level and speaking fundamental frequency was recorded. Acoustical analysis with long-term average spectrum was performed. Significant changes after therapy for the experimental group include the alpha ratio, L1–L0 ratio and ratio between 1–5 kHz and 5–8 kHz. The results indicate that the use of phonatory tasks with straw exercises can have immediate therapeutic acoustic effects in dysphonic voices. Long-term effects were not assessed in this study.